Rancang Bangun Aplikasi Penilaian Kinerja Berbasis Web Pada PT. Bhirawa Steel - Pambudi, Dwi Prasetyo; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT. Bhirawa Steel is one of the oldest and the most modern steel producer in Indonesia. Human resource divison of PT. Bhirawa Steel does performance appraisal manually with calculator, so that often happens 10% counting error while giving score of assessment and difficulty in recapitulating. Based on the problemes, so the solution can be offered is a web application of performance appraisal in PT Bhirawa Steel. This application use graphic rate scale method, in which the description of appraisal as measured by a scale that each has a point. In this case, used scale 1 until 4. The steps of planning system are block diagram, system flow, data flow diagram (DFD), entity relationship diagram (ERD), database structure and make a trial design. After doing trial, web application of performance appraisal can help a process of employee’s performance assessment accurately that previously were did manually. In addition, web application can help to determine a material of training for employees and give a overall report or report of each employee’s assesment, so can help human resource division to calculating assesment.